Islet Stellate Cells Isolated from Fibrotic Islet of Goto-Kakizaki Rats Affect Biological Behavior of Beta-Cell - Feng-Fei Li; Bi-Jun Chen; Wei Li; Ling Li; Min Zha; S. Zhou; M. G. Bachem; Zi-Lin Sun (Journal of Diabetes Research)
We previously isolated islet stellate cells (ISCs) from healthy Wistar rat islets. In the present study, we isolated “already primed by diabetic environment” ISCs from islets of Goto-Kakizaki rats, determined the gene profile of these cells, and assessed the effects of these ISCs on beta-cell function and survival. We detected gene expression of ISCs by digital gene expression. INS-1 cell proliferation, apoptosis, and insulin production were measured after being treated with ISCs supernatant (SN). We observed the similar expression pattern of ISCs and PSCs, but 1067 differentially expressed genes. Insulin production in INS-1 cells cultured with ISC-SN was significantly reduced. The 5-ethynyl-2′-deoxyuridine-positive INS-1 cells treated with ISC-SN were decreased. Propidium iodide- (PI-) positive INS-1 cells were 2.6-fold higher than those in control groups. Caspase-3 activity was increased. In conclusion, ISCs presented in fibrotic islet of GK rats might be special PSCs, which impaired beta-cell function and proliferation and increased beta-cell apoptosis.